Comparison of Modern and Traditional Pig Wastewater Treatment in Serian, Sarawak - Ainon, H.; Mohd-Jefrin,, A.A.; Ling, Teck Yee (Malaysian applied biology, 2005)
Pig farming is an important industry in Sarawak. Efforts have been made by pig farmers to treat pig wastewater by installation of oxidation ponds. However, little information is available on the effectiveness of the ponds installed. In this study, wastewater quality was investigated in two pig farms in Serian, Sarawak. Farms selected were a farm with 8,000 standing pig population (SPP) uses multiple pond system (fB farm) and another farm with 800 SPP use only one pond system (HB farm). The oxidation ponds ofTB farm reducedtSS, BODs, COD, and NH3-N by 54%, 39%, 35% and 56%, respectively, whereas in HB farm reductions were 29%, 15%, 10% and 9%, respectively. DO concentrations for TB farm and HB farm increased 40010 and 13%, respectively. Nitrate was reduced at 65% in the water samples of TB farm but there was an increase of 11% in the HB farm,effluent. Even though TB farm has ten times more SPP than HB farms, the final discharge from TB farm was of significantly better water quality than that of HB farm. It is recommended that at least three ponds of appropriate -size with separator be installed for the treatment of pig farm wastewater before being discharged into the river.